Seed Storage Behaviour of Tinospora sinensis - C.R. CHITRA,; C. ANIL KUMAR,; P.N. KRISHΝΑΝ, (Seed Research, 2026)
Tinospora sinensis propagates through stem cuttings and seeds. Desiccation sensitivity and effect of storage conditions on seed germinability shows that seeds are sensitive to freezing temperature. Optimum storage at 10°C and desiccation tolerance up to 6.8 per cent moisture content indicate the intermediate nature of seed storage. Storage of seeds with 6.8 per cent moisture content at 10°C in hermetically sealed containers is recommended for retaining the viability of seed for a longer period.